PROCESS ANALYSIS USING BUSINESS PROCESS MANAGEMENT - Pereira, João; Martins, A.; Pereira, R. (XVIII Encuentro Internacional AECA, 2018)
Business process management is widely used to improve companies’ competitive level. Incident management is a critical process as it supports the main services of an organization. Its speed and accuracy are paramount to companies. This research aims at analysing an incident management process of a global company and produce managerial recommendations on how to improve its performance. A case study approach is conducted. Process analysis is conducted based in interviews, direct observation, and focus group to assure data triangulation. Process improvement is based on the goals of the process and managerial recommendations are provided to support that improvement.